Randomised double masked trial comparing the efficacy and tolerance of 0.05% mequitazine eye drops versus 0.05% levocabastine and placebo in allergic conjunctivitis induced by a conjunctival provocation test with Dermatophagoides pteronyssinus. Issue 3 (20th February 2004) - Mortemousque, B; Jacquet, A; Richard, C; Depont, F; Colin, J; Moore, N
Abstract : Aim: A double masked randomised trial comparing 0.05% mequitazine eye drops with 0.05% levocabastine and placebo was carried out in otherwise heatlhy volunteers allergic to house dust mites ( Dermatophagoides pteronyssinus ). Method: Double masked, randomised, single centre study, comparing three parallel treatment groups. 60 healthy adults with a confirmed history of allergic conjunctivitis to house dust mites for at least 2 years were included and completed the trial. Conjunctival provocation tests (CPT) were done at screening, at visit 2 (V2) (1 week later), and at visit 3 (V3) (2 weeks after V2). Treatment was instilled in the same eye, 5 minutes after the CPT at V2, and twice daily until V3. CPT were scored 5, 10, 15, and 60 minutes after instillation of the dose of Dermatophagoides pteronyssinus antigen determined at inclusion (V2, curative test) or resulting in positivity (V3, preventive test) Results: In the V2 (curative) test the difference between the active treatments and placebo on the redness+itching scores was not significant. At the V3 (preventive) CPT there was a lower number of reactions at the threshold dose with mequitazine (20%) compared to placebo (60%, p = 0.01) or levocabastine (45%, p = 0.10). Conclusion: This trial failed to clearly demonstrate curative superiority of topical antihistamines with placebo, when a single dose of treatment was instilled following CPT. However mequitazine 0.05% eye drops were superior to placebo in preventing a reaction to CPT, after 2 weeks of treatment.